Behind The Broadcast: College Sports - Kiss, Hope Victoria (My University, 2024)
My Honors Creative Endeavor is a documentary about working in a sports broadcast. This is actually a job that I have had for over a year as an ECU student. It showcases what I do in the job: film, replay, dashboard, etc. It is from the perspective of my bosses and coworkers. They talk about what they do to bring ECU sports to ESPN+ with footage to support their claims. My project highly showcases my skills of videography and video editing. The documentary's interviews, videography, editing, and audio were done by me. https://www.youtube.com/watch?v=Z3p6wWWPvXI
Keywords: sports; broadcast; documentary; videography; editing